ANALISA FINITE ELEMENT METHOD (FEM) UJI BEBAN PADA MEJA POLYETHYLENE - Muhammad Fazly Arliansyah; Saputra saputra; Rahman Rahman; Widi Suyudi Ashari; Muhammad Zaki Prawira; Alyuan Dasira (JURNAL JALASENA, 2023)
FEM is an overall method based on an approach using numerical analysis. In this method, the structure to be analyzed is discretized into small elements (finite elements) which are connected to each other by nodal points (discrete points). The use of FEM analysis is also commonly used with the ANSYS workbench application. The use of the table is often found in everyday life. In this study, we will test the strength of a table made of polyethylene against a load of 5000N which will be applied to the surface of the table. The results to be taken from this study are the results of the deformation and equivalent stress of the table surface. After carrying out a load test of the size of the table using the ANSYS workbench software, the maximum deformation result for the table surface is 0.0086057 or 0.008 x 1000 = 8cm. Meanwhile, the equivalent stress result was 6.99 Pascals.